(untitled) (Research, Society and Development, 2021)
Agroforestry Systems (AFS) appears to enhance the productivity of agro-ecosystems and improve the financial gains of family farming. It is questioned in this study the effectiveness of the use of SAFs to increase the productivity and the financial income of small areas. Thus, the objective of the study is to evaluate the productive performance, the labor demand and the financial efficiency of the SAFs. The methodology was based on a case study, where during the period of six months information was collected through semi-structured interviews, as well as the daily routine of three farmers who are inserted in the context of the Contested Settlement, in the municipality of Lapa, Paraná. To perform the prognosis of the financial analysis, the AmazonSAF 8.1 spreadsheet was used. On the optimized model, from three accompanied farmers, the SAF-3 presented the best financial productive performance, exceeding 17 tons / 0.5 ha / year of food, which corresponds to a NPV of R 339,123.40 during the analyzed period with guaranteed sale by the National School Feeding Plan (PNAE). The demand for labor, in all SAFs, is concentrated in the cultivation of short-cycle species, reaching more than 200 daily working per year. It is concluded official financial indicators demonstrate financial viability for the three SAFs. But the cash flow does not demonstrate regular profitability from the eighth or ninth year until the 15th, because vegetable revenues were so high in the first years of cultivation that they managed to maintain positive financial indicators for the entire period.